1973
DOI: 10.1104/pp.51.4.660
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Accumulation of Microgram Quantities of Chlorophyll by Developing Chloroplasts in Vitro

Abstract: Developing chloroplasts were incubated under conditions previously shown to induce protochlorophyll and chlorophyll biosynthesis, as well as chloroplast maintenance and partial differentiation in vitro. In the presence of air, 6-aminolevulinic acid, coenzyme A, glutathione, potassium phosphate, methyl alcohol, magnesium, nicotinamide adenine dinucleotide, and adenosine triphosphate, microgram quantities of chlorophyll accumulated after 1 hour of incubation. Part of the chlorophyll was not extractable in organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This suggestion is supported by the observation that wild type cells, which synthesize chlorophyll in the dark (24,49), also are capable of making b and c in the dark. However, since the site of synthesis of chlorophyll is within chloroplasts (42,43), a mechanism by which synthesis ofb and c on cytoplasmic ribosomes can be controlled by chlorophyll or its precursors is not obvious. Moreover, it is not known whether b and c are primary products of translation or whether they are derived from a larger precursor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion is supported by the observation that wild type cells, which synthesize chlorophyll in the dark (24,49), also are capable of making b and c in the dark. However, since the site of synthesis of chlorophyll is within chloroplasts (42,43), a mechanism by which synthesis ofb and c on cytoplasmic ribosomes can be controlled by chlorophyll or its precursors is not obvious. Moreover, it is not known whether b and c are primary products of translation or whether they are derived from a larger precursor.…”
Section: Discussionmentioning
confidence: 99%
“…THE JOURNAL OF CELL BIOLOGY" VOLUME 70, 1976" pages 326-337 other membrane lipids are synthesized within the chloroplast (8,11,42,43), but the membrane proteins are synthesized both inside and outside the organelle (12,17,30). Indeed, as work on the effects in vivo of inhibitors of protein synthesis (10,13,17,21,30) and with isolated chloroplasts (4, 9) has shown, the major integral polypeptides of this membrane are synthesized outside the chloroplast on cytoplasmic ribosomes.…”
mentioning
confidence: 99%
“…This is indicated by the re cent findings of Henningsen & Kahn (66), who reported that protochloro phyll(ide) subunits of 60,000 to 100,000 molecular weight and presumably con taining one protochlorophyll chromophore per subunit were photoconverted. (128,130). 14(;-chlorophyll a formed from 14(;-ALA was purified to constant specific radioactivity and degraded to 14(; maleirnides (125).…”
Section: Reduction Of Protochlorophyll Holochromementioning
confidence: 99%
“…The enzyme was assayed in the presence of 0.1 % Triton X-lOO. Protoporphyrin IX was methylated at one tenth the rate of Mg protoporphyrin.In conclusion, all the evidence available so far derived fr om R. sp heroides chromatophores(43, 16 5), the solubilized Euglena enzyme (25), chloroplast preparations ( 119 ), and crude homogenates (3 1) fr om higher plants, indicate that Mg protoporphyrin is the best substrate fo r the methylation reaction.FORMATION OF PROTO CHLOROPHYLLAll the enzymes necessary for the formation of protochlorophyll fr om added ALA are obviously present in isolated etioplasts (Rebeiz & Caste1franco 124) and developing chloroplasts(Rebeiz et al 128,130). It was shown that crude cotyledonary homogenates as well as isolated etioplasts were capable of convert ing HC-ALA into HC-protochlorophyllide (IXb) and HC-protochlorophyllideester (IXc) (124).…”
mentioning
confidence: 97%
“…The total amount of Chl was calculated after Bruinsma (1963) and is given in mg per 30 cotyledons. We were unable to extract either Pchl or Chl from plants irradiated for periods up to 8 h. Rebeiz et al (1973) could not extract Chl completely with organic solvents from isolated Cucumis chloroplasts after in oitro incubation, whereas Hardy et al (1970) extracted Chl with acetone from Cucumis cotyledons. In those cases where pigments could not be extracted, the relative pigment content was obtained by measuring the absorbance of the cotyledons in uivo.…”
Section: Methodsmentioning
confidence: 80%